Investigative and research learning technology - Aizhan Esetovna Kazhenbaeva, Svetlana Sanzhanovna Kulmagambetova, Kulyash Temirgaliyevna Bainiyeva,; Kaparovna Yelezhanova, Shynar (Opción, 2019)
The study aims to examine investigative and research learning technology via comparative qualitative research methods. Approaches to the formation and implementation of the training process are determined by what is chosen as the essential unit of education. As a result, tasks, as a rule, are based on the initial level but have the direction to achieve the highest level of knowledge among students, in other words, the task consists of an initial level and a perspective level. In conclusion, we can say that it has a dual character, inconsistency, which is the impetus for better learning.